OPTIMALISASI PENGGUNAAN TEKNOLOGI DALAM PEMBELAJARAN DEEP LEARNING UNTUK MENINGKATKAN KOLABORATIF SISWA PAUD - Sari, Loulyta; Ristiana, Yayan; Yayuk, Erna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study seeks to explore and enhance the integration of technology in deep learning to support the development of collaborative skills among Early Childhood Education (ECED) students. In the digital era, technology integration is an important aspect of learning that encourages active engagement, critical thinking and collaboration from an early age. The method used in this research is a qualitative approach using a case study design, which includes observation, detailed interviews, and documentation at two early childhood education institutions that have integrated technology into their learning processes. The results show that the use of interactive technologies such as smart boards, educational apps, and project-based digital media can create a collaborative and participatory learning environment. There was noticeable improvement in children's teamwork, including their ability to share ideas and complete activities collaboratively. However, barriers such as insufficient resources and lack of teacher readiness still persist. Therefore, teacher training and the provision of adequate infrastructure are key in optimizing the application of technology. This study concludes that technology, if used appropriately within the framework of deep learning, has great potential to effectively foster early childhood collaborative skills